Equity and Efficiency of Koreans' English Education Investments - Hisam Kim (Korea Development Institute (KDI), 2012)
- Need to assess equity and efficiency of investment of time, effort, and money into Koreans' development of English ability from standpoint of economic resource allocation - One-third of all primary and secondary school students' private tutoring expenditures go toward English study; college students and adults also invest substantial time and effort in English learning - Equity Issue: So-called "English gap" between income classes and across regions - There exist large disparities in private education investment between income groups and differing degrees of English exposure across regions despite similar income levels - Large class- and region-based differences in English scores on National Assessment of Educational Achievement (NAEA), College Scholastic Ability Test (CSAT), and Test of English for International Communication (TOEIC) - English ability more strongly influenced by environment than other subjects and used as screening device for entrance to colleges and companies, indicating significance in terms of equality of opportunity - Three questions associated with efficiency of resource allocation for English education: (1)To what extent are people rewarded in the labor market for their English education investments? (2)Is it desirable to have English-related experience used as a device for screening and signaling? (3)Are employees' English abilities matched with the needs of their position? - English experience beneficial in job applicant screening and interviews, but TOEIC score found to be more important in determining full-time employment status, workplace scale, and salary - Wage premium for English proficiency may be associated more with worker's other capabilities than English-related productivity improvements ·No connection observed between premium and job demands for English proficiency ·College students found to sacrifice studies and activities in other areas due to their perception that companies value English-related experience - Mismatch between workplace English demands and employee proficiency by job type ·Lower frequency of use in business/clerical positions relative to high levels of investment and proficiency owing to demands for related experience in application process ·Far lower investment and proficiency than needed for positions in sciences and medicine/pharmaceuticals ·Need for rethink practice of using English as a screening device for gauging the abilities of liberal arts (as opposed to science) students - Rational, ongoing efforts required from primary/secondary schools, universities, companies, and government to enhance equity and efficiency of investments in English education - Schools: Promote practicality of English teaching and prevent English gap from growing - Universities: Prevent English study from interfering with development of other student capabilities - Companies: Demand appropriate level of English proficiency for position - Government: Promote equity and efficiency of investment through improvements to public education and hiring practices
Keywords: 330